SEJARAH PERKEBUNAN DAN DAMPAKNYA BAGI PERKEMBANGAN MASYARAKAT DI ONDERAFDEELING BANJOEASIN EN KOEBOESTREKKEN, KERESIDENAN PALEMBANG, 1900-1942 - zusneli zubir (JURNAL PENELITIAN SEJARAH DAN BUDAYA, 2019)
The purposeandobject ofthis paperisarelevancebetween the existence oflarge estates, Onderneming Europeandits impact on societyin Onderafdeeling Banjoeasinen Koeboestrekenthe colonial periodin1900-1942. The method usedin this studyis the historical method to reconstruct the history of the plantationand the implications forthe development of society in Onderafdeeling Banjoeasinen Koeboestrekken. Data collection techniques use drefersto the first stage in the history ofthe process of heuristic methods, finding and collecting historical sources. Data analysis techniques with regard to the second stage, third and fourth in the history covering methods of source criticism, and historiography interpretation. Based on the research results and conclusions, the opening rubber plantations in the colonial period Onder afdeeling Banjoeasinen Koeboe strekken highly correlated with the natural conditions of this area and also the political changeskonial, open the door. There are two big companies that invest heavily large plantations of rubber namely, first, Rubber Ondernemingen Melaniain 1909 the plantingand effort trubber massively from the east end of Marga Pangkalan Balai to the west endMarga Gasing and centered in Musi Landas. Secondly, plantation Oud Wassenaar, N.V. Oliepalmenen rubber Mijnsprawling in the gutter are as ranging northern Batang Hari Leko, Marga Rantau Bayur, toits northern Marga Suak Tape, Marga Betung and Tebenan area. The relevance of the opening of a large estate with acommunity in Onder afdeeling Banjoeasinen Koeboe strekkenseenin some ways. First, the change in the position of the local elite, the Pasirah, Kerio, others Marga council officials. Secondly, helped create the “repair” the public infrastructure facilities and infrastructures there. Third, encourage the development ofeconomic activity and providea tremendous impact in the dusun-dusun marga’s. Fourth, many builders connecting road for the purposes of transportation of rubber has abroad and profound impacton the pattern of a traditional society, not only for the Malays Banjoeasin, but also to aspects of the life of the Kubu’s Banjoeasin. They began the gradual assimilation are creating Kubu’s Banjoeasin with Malay Banjoeasin due to changes in the orientation of his thinking because it began opening their areas of influence of the outside world.